Characteristics of electrolysis, ozonation, and their combination process on treatment of municipal wastewater - Kishimoto, Naoyuki (Water environment research : a research publication of the Water Environment Federation, 2007)
The characteristics of municipal wastewater treatment by electrolysis, ozonation, and combination processes of electrolysis and aeration using three gaseous species (nitrogen [N2], oxygen [O2], and ozone [O3]) were discussed in this research using ruthenium oxide (RuO2)-coated titanium anodes and stainless-steel (SUS304) cathodes. Electrolysis and electrolysis with nitrogen aeration were characterized by a rapid decrease in 5-day biochemical oxygen demand (BODs) and total nitrogen and a slow decrease in chemical oxygen demand (COD). In contrast, ozonation, electrolysis with oxygen aeration, and electrolysis with ozone aeration were characterized by transformation of persistent organic matter to biodegradable matter and preservation of total nitrogen. The best energy efficiency in removing BOD5 and total nitrogen was demonstrated by electrolysis, as a result of direct anodic oxidation and indirect oxidation with free chlorine produced from the chloride ion (Cl-) at the anodes. However, electrolysis with ozone aeration was found to be superior to the other processes, in terms of its energy efficiency in removing COD and its ability to remove COD completely, as a result of hydroxyl radical (*OH) production via cathodic reduction of ozone